Chemical warfare agent simulants for human volunteer trials of emergency decontamination: A systematic review. Issue 1 (9th October 2017) - James, Thomas; Wyke, Stacey; Marczylo, Tim; Collins, Samuel; Gaulton, Tom; Foxall, Kerry; Amlôt, Richard; Duarte‐Davidson, Raquel
Abstract: Incidents involving the release of chemical agents can pose significant risks to public health. In such an event, emergency decontamination of affected casualties may need to be undertaken to reduce injury and possible loss of life. To ensure these methods are effective, human volunteer trials (HVTs) of decontamination protocols, using simulant contaminants, have been conducted. Simulants must be used to mimic the physicochemical properties of more harmful chemicals, while remaining non‐toxic at the dose applied. This review focuses on studies that employed chemical warfare agent simulants in decontamination contexts, to identify those simulants most suitable for use in HVTs of emergency decontamination. Twenty‐two simulants were identified, of which 17 were determined unsuitable for use in HVTs. The remaining simulants ( n = 5) were further scrutinized for potential suitability according to toxicity, physicochemical properties and similarities to their equivalent toxic counterparts. Three suitable simulants, for use in HVTs were identified; methyl salicylate (simulant for sulphur mustard), diethyl malonate (simulant for soman) and malathion (simulant for VX or toxic industrial chemicals). All have been safely used in previous HVTs, and have a range of physicochemical properties that would allow useful inference to more toxic chemicals when employed in future studies of emergency decontamination systems. Abstract : To conduct human volunteer trials on the decontamination of chemical warfare agents, simulant chemicals that mimic the properties of the live agents must be used. For the first time, this review identifies previously used chemical simulants and assesses their suitability according to toxicity, physicochemical properties and similarity to their equivalent toxic counterparts.